2011
DOI: 10.1117/12.894379
|View full text |Cite
|
Sign up to set email alerts
|

The alignment of the aerospace Cassegrain telescope primary mirror and iso-static mount by using CMM

Abstract: In order to meet both optical performance and structural stiffness requirements of the aerospace Cassegrain telescope, the primary mirror shall be mounted with the main plate by iso-static mount. This article describes of the alignment of the aerospace Cassegrain telescope's primary mirror and iso-static mount by using coordinate-measuring machine (CMM), and the design and assembly of mechanical ground support equipment (MGSE). The primary mirror adjusting MGSE consists of three 3-axis linear stages and point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Howick et al (2007) 3 showed that CMM can be used in the metrology of lenses and alignment process. Lin et al (2011) 4 also used a CMM machine to verify the orientation of the Cassegrain telescope's primary mirror and the orientation adjustment of its mechanical ground support equipment. Lin et al (2012) 5 expanded their previous work by using a CMM to verify the bonding technique of the space telescope.…”
Section: Introductionmentioning
confidence: 99%
“…Howick et al (2007) 3 showed that CMM can be used in the metrology of lenses and alignment process. Lin et al (2011) 4 also used a CMM machine to verify the orientation of the Cassegrain telescope's primary mirror and the orientation adjustment of its mechanical ground support equipment. Lin et al (2012) 5 expanded their previous work by using a CMM to verify the bonding technique of the space telescope.…”
Section: Introductionmentioning
confidence: 99%
“…W.C. Lin and S.T. Chang presented the alignment procedure of primary mirror of cassegrain telescope by using CMM, and the post-analyzing algorithm of optical parameter from the CMM measured raw data by using optical software is precise and useful for the alignment of the mid-large opto-mechanical system 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The method is a precise and useful method for aligning mid-size to large optomechanical systems. 5,6 Kihm et al proposed a novel design for adjustable bipod flexures used to mount mirrors and conduct optical experiments on a space telescope. The design reduced the error caused by the gravity effect to less than root mean square 10 nm.…”
mentioning
confidence: 99%